2014
DOI: 10.1142/s0219887814500686
|View full text |Cite
|
Sign up to set email alerts
|

Emergent quantum mechanics as a thermal ensemble

Abstract: It has been argued that gravity acts dissipatively on quantum-mechanical systems, inducing thermal fluctuations that become indistinguishable from quantum fluctuations. This has led some authors to demand that some form of time irreversibility be incorporated into the formalism of quantum mechanics. As a tool towards this goal we propose a thermodynamical approach to quantum mechanics, based on Onsager's classical theory of irreversible processes and on Prigogine's nonunitary transformation theory. An entropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…It is well-known that for an uniformly accelerated observer, the fluctuations of a quantum field in the inertial vacuum state appear to be identical to the thermal fluctuations of an real thermal bath indicating some kind of equivalence between thermal and vacuum fluctuations [1,2]. There have also been suggestions that quantum and statistical fluctuations, including thermal ones, are essentially identical [3] (see also [4]). In a recent paper [5], we explored this relationship between thermal and quantum fluctuations beyond the context of the vacuum state.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that for an uniformly accelerated observer, the fluctuations of a quantum field in the inertial vacuum state appear to be identical to the thermal fluctuations of an real thermal bath indicating some kind of equivalence between thermal and vacuum fluctuations [1,2]. There have also been suggestions that quantum and statistical fluctuations, including thermal ones, are essentially identical [3] (see also [4]). In a recent paper [5], we explored this relationship between thermal and quantum fluctuations beyond the context of the vacuum state.…”
Section: Introductionmentioning
confidence: 99%
“…This defines both quantum dynamics in (17) and the entropy-action proportionality for the Einstein-Hilbert action S EH (4):…”
Section: α and Holographic Gravitymentioning
confidence: 99%
“…However, as regards entropy, a complete covariant theory of thermodynamics and statistical mechanics in a full general relativistic context is yet to be established [15]. Initial investigations have shown that for a constant "thermal time" there seems to be a direct relation between temperature and inverse proper time [15,16,17]. With the assumption that entropy is negative information I there is also a direct connection between entropy, energy E and time t in upper limits of the bound on the information I transfer in black hole thermodynamics [18]:…”
Section: Introductionmentioning
confidence: 99%